Reinforcement Positioning in Custom-Made Mouthguards for Maxillofacial Trauma Protection: A Combined In Vitro and In Silico Analyses - de Queiroz, Talita Suelen [UNESP]; Tribst, João Paulo Mendes; Haddad e Borro, Larissa [UNESP]; da Rocha Scalzer Lopes, Guilherme [UNESP]; Borges, Alexandre Luiz Souto [UNESP]; de Arruda Paes Junior, Tarcisio Jose [UNESP] (Wiley, 2025)
Background/Aim: This study evaluated the dentoalveolar responses of central incisors to anterior maxillary trauma in vitro and in silico using mouthguards (MGs) reinforced with polyamide mesh at three distinct positions. Material and Methods: Forty 4-mm thick MGs were categorized based on mesh location: Group MG1 + 3 (reinforcement 1 mm from the vestibular limit), Group MG2 + 2 (2 mm), Group MG3 + 1 (3 mm), and a control group without reinforcement. A 3D-printed skull model (Spin Red Resin, Quanton 3D) simulated the dentoalveolar complex, with Resilab Clear resin (Wilcos) for teeth and addition-cured silicone for the periodontal ligament. This setup was connected to a custom impact device to ensure forces remained within the materials' elastic limits. Microstrains were measured using four strain gauges placed on the vestibular surfaces of the central incisors and the alveolar process of the maxilla. The impact was applied at Ep = 0.5496 J, parallel to the ground, using a 35-mm diameter steel sphere. For the in silico test, the setup was modeled in CAD software (Rhinoceros 7.0) and analyzed in CAE software (Ansys 2021 R1) through explicit dynamic simulation. All materials were assumed homogeneous, isotropic and linearly elastic. A 1 m/s impact was simulated using a 7.8 g/cm3 steel sphere. Physical contact conditions were defined as frictional and glued, with tetrahedral mesh elements applied after a 10% convergence test to ensure accuracy. Results: The maximum principal strains and stresses in teeth and maxilla were presented through colorimetric graphs. Statistical analysis (Shapiro–Wilk, Kruskal–Wallis, and Dunn's tests, 5% significance) revealed significant differences for the non-reinforced group (p = 6.8 × 10−5) but none between impact zones (p = 0.879), confirming uniform stress distribution. Conclusions: Reinforcement systems significantly improved impact absorption in oral tissues, enhancing protection. However, the reinforcement location did not significantly affect absorption. Finite element analysis validated the in vitro results supporting both theoretical and practical models for further study and future improvements.
Keywords: biomechanical response; dental trauma; finite element analysis; mouthguard; reinforcement mesh